Literatur Review: The Effect Of Stress During Pregnancy On Pregnancy Outcomes - Dewi Pitriawati; Dwi Sri Rahandayani (Jurnal Genta Kebidanan, 2021)
The CoViD-19 pandemic requires many people to be able to adapt significantly to all changes. Pregnant women are also required to be able to adapt to everything that happens, this often puts pregnant women at risk of experiencing problems or psychological disorders because of the adaptation process that requires a lot of energy. Psychological problems or disorders such as stress are feared to have an effect on the health condition of the mother and fetus during pregnancy. This study aims to find out the influence of pregnancy stress on pregnancy outcomes. This research method is a reviewed literature that conducts searches in gscholar and pubmed with a system of article elimination according to the criteria of inclusion, exclusion and feasibility of literature. Library searches in this study successfully identified 9 articles that discussed the influence of stress in pregnancy on pregnancy outcomes. Problems, stress or psychological disorders in pregnancy can cause various health problems for both the mother and fetus, therefore the need to maintain the quality of the mother's mental health during pregnancy for the quality of maternal and fetal health during pregnancy and postpartum period.